Extractive Spectrophotometric Determination of Nortriptyline Hydrochloride Using Sudan II, IV and Black B - A. S. Amin; H. M. Saleh (MDPI AG, 2017)
A simple spectrophotometric methods has been developed for the determination of nortriptyline hydrochloride in pure and in pharmaceutical formulations based on the formation of ion-pair complexes with sudun II (SII), sudan (IV) (SIV) and sudan black B (SBB). The selectivity of the method was improved through extraction with chloroform. The optimum conditions for complete extracted colour development were assessed. The absorbance measurements were made at 534, 596 and 649 nm for SII, SIV and SBB complexes, respectively. The calibration graph was linear in the ranges 0.5- 280. 0.5- 37.5 and 0.5 - 31.0 μg ml−1 of the drug usiny the same reagents, respectively. The precision of the procedure was checked by calculating the relative standard deviation of ten replicate determinations on 15 μg ml−1 of nortriptyline HCI and was found to be 1.7, 1.3 and 1.55% using SII, SIV, and SBB complexes, respectively. The molar absorptivity and Sandell sensitivity for each ion-pair were calculated. The proposed methods were successfully applied to the deterniination of pure nortriptyline HCI and in pharmaceutical formulations, and the results demonstrated that the method is equally accurate, precise and reproducible as the official method.